ANALISA PENGARUH JUMLAH LILITAN STATOR TERHADAP GENERATOR MAGNET PERMANEN FLUKS RADIAL TIGA FASA - Ahmad Sauky Al Farisi; Alex Wenda; Lili ana; Nanda Putri Miefthawati (Power Elektronik : Jurnal Orang Elektro, 2021)
Abstract - Magnetic generator is a synchronous generator that uses permanent magnets to generate magnetic flux. In its manufacture, to increase the power, voltage and speed of a permanent magnet generator, simply change parameters such as magnetic flux, number of turns, number of turns, number of magnets and wire diameter. To design or analyze permanent magnet generators,used software is MagNet 7.5to simulate it. This magnet software is based on the Finite Element Method or commonly called FEM. FEM is a computational method that has the concept of breaking the calculation area into small parts and then calculating the parameters one by one in each part. In this study, the variables to be simulated are the number of turns on the stator coil with a variation of 10, 50, and 75 turns. This study uses a combination of 18 slots 16 poles with NdFeB magnets. Then the generator is tested using a 20 ohm load. From the simulation, it can be seen that the number of turns affects the voltage and power generated, where when the generator is given a 20 ohm load with 10, 50, and 75 turns it produces a voltage of 22.3 volts, 88.9 volts and 103.7 volts then for power it produces 61.2 watts, 547 watts and 756.2 watts.Keyword - Coil, MagNet 7.5, Power, Voltage